Patient satisfaction of outpatient department at ESIS hospital, Nagpur, India - Deshmukh, Meena A.; Upadhye, Jayshree J. (International Journal of Research in Medical Sciences, 2019)
Background: Employee state insurance scheme (ESIS) is a multidimensional social security system providing medical facilities to the insured persons and their family through large network of hospitals and dispensaries all over India. The present study was done to measure the satisfaction of OPD (Outpatient Department) patients. Methods: A descriptive cross-sectional study was conducted in ESI Hospital, Nagpur, Maharashtra, India on 500 patients attending OPD. Patients were approached at the end of their OPD visits to know their perceptions towards the public health facilities, during the months of September and October 2017. Data collected was analyzed. Results: In present study, out of 500 patients, 210 (42%) said that crowd was average, 270 (54%) were satisfied with queue system, 390 (78%) were satisfied with the availability of drugs, 380 (76%) were satisfied with the behaviour of pharmacist.205 (41%) patients said it was not overcrowded, 310 (62%) patients were happy with the behaviour of registration clerk, 330 (66%) were satisfied with the seating arrangements for the patients and attendants, 265 (53%) were satisfied with the cleanliness, 205 (41%) were satisfied with the condition of toilets. 390 (78%) patients said that doctor was available, 270 (54%) said that waiting time was less, 325 (65%) said that doctor listened to the problem attentively, 435 (87%) said that the doctor explained nicely about the disease while 425 (85%) were satisfied with the time given by the doctor. Conclusions: Almost half of the patients were satisfied with the registration facilities, basic amenities, service by doctor and pharmacy services. Mostly, patients chose this hospital as it was free for them due to their insurance and as it was near their house. Still, there is scope for improvement.